“It seems like it should be so simple”: the role of the family in elder driving retirement - Frost-Steward, Jill M. (Kansas State University, 2015)
Due to health conditions, the average 70 year old will outlive the ability to drive by 6 years for men and 10 years for women (Foley et al., 2002). Driving loss has a significantly negative impact on the quality of life of an older adult. For this reason, some continue to drive despite concerns about safety. Midlife family members of older adults often feel social pressure to intervene in driving decision-making and social pressure to refrain from intervening. The goal of this study was to understand the experiences of midlife family members from the time that someone first noticed a concern with the older relative’s driving until the time the older adult stopped driving. A qualitative, multiple embedded case study approach was used to gather information from two midlife family members from 7 families with an older driver who had recently retired from driving. The family processes that influenced communication about driving and choice of strategies for intervening were examined. Findings indicated that the midlife family members became aware of safety issues at different times. Awareness prompted conversations with other relatives, and the majority of family conversations about driving did not include the older adult. Many family members reported a respect for the autonomy of the older relative and a reluctance to initiate conversations without permission from the older adult to do so. Intervention strategies reported by participants included (1) wait and worry, (2) nudging, (3) attempted conversation, (4) ending requests for driving assistance, (5) requesting assistance from physicians, (6) requesting assistance from the DMV, (7) requesting assistance from law enforcement, and (8) accepting the inability to end an older adult’s driving career. Participants reported many factors that both helped and hindered efforts to encourage driving retirement. Based on these findings, an Ecological Model of Later-Life Decision-Making was proposed. The model reflects that the participants’ efforts to encourage driving retirement were not simply a matter of intra-family communication, but were influenced by processes occurring at multiple levels, both within and outside of the family. Processes occurring at multiple levels both helped and hindered family members’ efforts to encourage driving retirement.
Keywords: Driving Cessation; Family Communication; Intergenerational Influence; Older Drivers; Autonomy; Safety; Individual & Family Studies (0628)